2023
DOI: 10.3390/atmos14040755
|View full text |Cite
|
Sign up to set email alerts
|

Past and Future Responses of Soil Water to Climate Change in Tropical and Subtropical Rainforest Systems in South America

Abstract: The present study aimed to contribute to the diagnosis and advance the knowledge of the impacts of land use change and climate change on the tropical longleaf forest biome at the continental scale in South America (Biome 1 according to the WWF classification) for realizing scientific progress in the search for convincing strategies and actions by different actors for the preservation of forests in the continent. The status and climate of the area, which harbors the tropical longleaf forests of South America, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…The fire foci found in Rio Branco were concentrated in September, during the dry season, a result similar to that observed in similar studies carried out in the same region [23,26,36]. The results also showed that the land use most susceptible to fire was the lowland dense ombrophilous forest, a result similar to that found by [23].…”
Section: Forest Fires and Anthropic Advance In The Western Amazonsupporting
confidence: 88%
See 1 more Smart Citation
“…The fire foci found in Rio Branco were concentrated in September, during the dry season, a result similar to that observed in similar studies carried out in the same region [23,26,36]. The results also showed that the land use most susceptible to fire was the lowland dense ombrophilous forest, a result similar to that found by [23].…”
Section: Forest Fires and Anthropic Advance In The Western Amazonsupporting
confidence: 88%
“…The state is located in the northern region of Brazil (Figure 1), has 22 municipalities in an area of 164,173 km 2 , and an estimated population in 2022 of 830,018 inhabitants [25]. It is located in the Brazilian Amazon rainforest, bordering the state of Amazonas to the north and east and Bolivia and Peru to the south and west [26].…”
Section: Study Areamentioning
confidence: 99%